Metformin and Vitamin B12 Deficiency – What is the Evidence? - Peixoto, Bruno Daniel Oliveira; Gonçalves, Mariana Abreu; Gonçalves, Teresa Filipa Ramôa; Sá Martins, Aníbal Alberto (Scripta Medica, 2024)
The widespread adoption of metformin as a primary therapeutic agent for type 2 diabetes has prompted inquiries into its potential impact on vitamin B12 (cobalamin) levels and subsequent deficiency. This study aimed to elucidate this complex relationship and enhance the care provided to patients undergoing metformin treatment. A comprehensive search of meta-analyses, systematic reviews, randomised controlled trials and guidelines published between January 2010 and September 2021 was conducted. MeSH terms 'metformin' and 'vitamin B12,' along with corresponding DeCS terms, guided the search. Varied recommendations from different scientific associations underscore the need for regular monitoring of vitamin B12 levels in patients undergoing long-term metformin therapy. Different durations of metformin exposure, spanning from 6 weeks to 48 months, were associated with decreased vitamin B12 concentrations. Observed decreases in B12 concentrations ranged from 7.7 to 65.8 pmol/L, with percentage reductions ranging from 6.3 % to over 35 %. The evidence highlights a dosage-dependent correlation between higher metformin doses and an increased prevalence of B12 deficiency. The results obtained highlight the association between metformin and B12 deficiency. The prevalence of B12 deficiency under metformin is of a greater magnitude than the one declared on the Summary of Product Characteristics approved by the medicine regulatory agencies. Thus, clinicians should be aware of this possible side effect when prescribing metformin, in order to prevent, monitor and treat if present.
Keywords: Metformin; Vitamin B12; Diabetes mellitus